Adult Education and the Struggle for Knowledge and Power: Practical Action in a Critical Tradition - Arthur L. Wilson; Ronald M. Cervero (Adult Education Research Conference, 2001)
Along with others we argue that practical space can be found in nearly all forms of adult education for the redistribution of knowledge and power. The purpose of the paper is to describe a way of understanding practical action in a world structured by the inequitable distribution of knowledge and power.